Sensorivm (Leiden ; Boston)
xv, 458 sayfa
Keywords: “SENSORIVM: The Senses in Roman Polytheism explores how a range of cults and rituals were perceived and experienced by participants through one or more senses. The present collection brings together papers from an international group of researchers all inspired by 'the sensory turn'. Focusing on a wide range of ritual traditions from around the ancient Roman world, they explore the many ways in which smell and taste, sight and sound, separately and together, involved participants in religious performance. Music, incense, images and colors, contrasts of light and dark played as great a role as belief or observance in generating religious experience. Together they contribute to an original understanding of the Roman sensory universe, and add an embodied perspective to the notion of Lived Ancient Religion.“ --